DEVELOPMENT OF INFORMATION DISSEMINATION SYSTEM THROUGH SMS GATEWAY FOR COMMUNITY SERVICE (LPM) OF UNIVERSITY OF LAMPUNG - Dian Kurniasari; Kurnia Muludi; Evita Fitriasari (Universitas Lampung, 2015)
Community service programs is one of the three core services (Tri Darma) which is coordinated by LPM of the University of Lampung. Since there are large number of lectures who follow LPM Program, it is needed to have a special strategy for providing a means of dissemination of information to them. One of the technologies that are very popular among cell phone users is SMS (Short Message Service). The natures of SMS are practical, economical, and efficient to deliver information. SMS is a technology that is used by many people. It is also relatively cheap for message delivery. In this research, Information dissemination system with SMS Gateway is implemented using Gammu and is combined with PHP programming language and MySQL database. The results of the implementation of the system is helpful and easy for lectureres to obtain information about the program of community service where they are joined to.Keywords: Gammu, LPM, MySQL, PHP, SMS (Short Message Service), SMS Gateway.